On the history of biological drugs: the true discovery of the IL-1 receptor antagonist On the history of biological drugs: the true discovery of the IL-1 receptor antagonist - P. Marson; L. Punzi (PAGEPress Publications, 2012)
Pasero, Marson and Gatto have recently published their article about the introduction of biological drugs in the field of rheumatology. The discovery of the IL-1 receptor antagonist (IL-Ra) is attributed to a group of researchers in Denver led by William P. Arend.... Pasero, Marson and Gatto have recently published their article about the introduction of biological drugs in the field of rheumatology. The discovery of the IL-1 receptor antagonist (IL-Ra) is attributed to a group of researchers in Denver....